(untitled) (Global Journal of Medical Research, 2013)
Osteoporosis (pronounced as ahsteoporosis) is characterized by low bone mass with micro architectural deterioration of bone tissue leading to enhance bone fragility, thus increasing the susceptibility to fracture. Although exact numbers are not available, based on available data and clinical experience, 25 million Indians may be affected. Osteoporotic fractures in India occur in both sexes but are more common in females. It may occur at a younger age in India than in the West. The pharmacological interventions are expensive with limited or no cure promise, and the peak bone mass of the population can be increased significantly by appropriate and timely intervention in children. So, the public health measures that are efficacious, safe and cost-effective, must be adopted for the population at large. This calls the attention of the physicians of all the systems of medicine including Greek-o-Arabic (unani) system. Although, there is no description of osteoporosis in Greek-o-Arabic (unani) classical literature yet, the debility of body organs including bones is widely discussed. It is generally said that ’prevention is better than cure’, so a specific prevention plan must be structured as per Greek-o-Arabic norms. Nevertheless, before making the prevention plan one must understand the Greek-o-Arabic etiopathology of the disease. Therefore, this work is an attempt to understand the underlying causes and risk factors of osteoporosis, and to construct a mighty prevention plan. To keep the Greek-o-Arabic spirit alive, the typical Greek-o-Arabic terms are not translated into English.